Primary Pleural Extranodal Marginal Zone Lymphoma Presenting as Bilateral Chylothorax - Paul, Thushara (Case Rep Oncol, 2020)
Here we describe a case of pleural extranodal marginal zone lymphoma presenting as bilateral chylothorax which has not been reported in the literature prior to this. Primary pleural lymphomas are a rare entity most commonly associated with chronic infections, autoimmune conditions or long-standing pyothorax which were not seen in this case. Chylous pleural effusions in this patient were successfully managed with chemotherapy for the underlying lymphoma.